ISOLASI DAN IDENTIFIKASI SENYAWA ANTIOKSIDAN DARI BATANG PAKIS (Alsophila glauca J.Sm) DENGAN METODE DPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) - Sri Wahdaningsih; Subagus Wahyuono; Erna Prawita Setyowati (Majalah Obat Tradisional, 2013)
Oxidative stress induced by the radicals have been known to affect the occurrence of various degenerative disease. In order to search natural antioxidant compounds, it had been studied the isolation and identification of antioxidant compounds in fern stems (Alsophila glauca J.Sm) using DPPH method (1,1-diphenyl-2-picrylhydrazyl). Fern stem extraction was done by maceration with wasbenzen and metanol. Extracts was obtained by evaporating the wasbenzen solvent with a rotavapor. Material was re-macerated with methanol after wasbenzen evaporation. The same way was done to obtain the metanol extract. These extracts were tested for antioxidant activity using DPPH method with TLC. Active extract was partitioned in 80% methanol. Both 80% methanol soluble and insoluble extract were tested their antioxidant activity using DPPH method (TLC). Active extract was fractionated in vacuum liquid chromatography using a mobile phase with different polarity gradient and different concentrations (wasbenzen:chloroform). Active fraction was isolated by preparative TLC method and purity of obtained compounds was tested by TLC. Antioxidant activity of obtained isolates was tested by DPPH method using spectrophotometry. Compounds known to had antioxidant activity as radical catcher with IC50 178.4µg/mL.